Efficacy and Safety of Brucea javanica Oil Emulsion Injection in the Treatment of Gastric Cancer: A Systematic Review and Meta-Analysis - Wang, Xinmiao; Wang, Heping; Cao, Luchang; Wu, Jingyuan; Lu, Taicheng; Li, Shixin; Li, Jie (Frontiers in Nutrition, 2021)
Background: Gastric cancer (GC) is one of the most common digestive tract cancers and ranks fifth in the incidence of malignant tumors worldwide. Brucea javanica oil emulsion injection (BJOEI), a Chinese patent medicine, is widely used as an adjuvant treatment for GC in China. This study aimed to evaluate the available data on the efficacy and safety of BJOEI in the treatment of GC and assess the quality of the synthesized evidence. Methods: A comprehensive search was performed on PubMed, EMBASE, CENTRAL, Web of Science, Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), Wanfang database and Chinese Scientific Journals Database (VIP database), and other potential resources, such as the Chinese Clinical Trial Registry (ChiCTR), and ClinicalTrials.gov from their inception to July, 2021. Randomized controlled trials (RCTs) comparing the therapeutic effects of BJOEI combined with conventional therapy to those of conventional therapy alone were included. We used RevMan 5.3 for data analysis and quality evaluation of the included studies and assessed the evidence quality based on the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Results: Eighteen RCTs involving 1,210 patients were included, and the meta-analysis results demonstrated that compared with the control group (conventional therapy), the experimental group (BJOEI combined with conventional therapy) showed significantly improved objective response rate (ORR) (RR = 1.52, 95% CI: 1.36~1.69, P < 0.00001), clinical benefit rate (CBR) (RR = 1.17, 95% CI: 1.11~1.23, P < 0.00001), performance status (RR = 1.72, 95% CI: 1.46~2.01, P < 0.00001), and reduced incidence of the following adverse drug reactions (ADRs): neutropenia, leukopenia, nausea and vomiting, diarrhea, liver damage, hand-foot syndrome, and peripheral sensory nerve toxicity. Subgroup analysis showed that the BJOEI intervention could significantly improve the ORR and CBR in GC patients when combined with FOLFOX4, XELOX, and other chemotherapeutics. Conclusion: The evidence presented in this study supports that BJOEI combined with conventional chemotherapy provides a statistically significant and clinically important effect in the improvement of ORR, CBR, performance status, and ADR reduction in patients with GC. To further support this conclusion, more rigorously designed, large-scale, and multicenter RCTs are needed in the future.